(untitled) (International Journal of Advanced Research in Computer Science, 2017)
In this paper, CPW design of microstrip patch antenna for WLAN standard is presented. The proposed design consists of Pi structure and circle which are designed on FR4 substrate. This paper holds the parametric study of different antenna parameters. The proposed structure is providing frequency bands from 2.35-2.84 GHz, 4.25-4.64 GHz, 5.14 -5.83 GHz such that total bandwidth is 1.57 GHz or 31.5%.The antenna performance antenna parameters like radiation pattern and antenna gain also presented in this paper. Keywords: WLAN, Microstrip Antenna and Pi Shape.